Analisis Benefit Incidence terhadap Kebijakan Subsidi Pupuk (Studi Kasus Desa Sidowayah Kecamatan Polanharjo Kabupaten Klaten) - Sukma Dwijayanti; Banatul Hayati (Universitas Diponegoro, 2020)
This study aims to determine the progressivity of the fertilizer subsidy policy and its effectivity in Sidowayah Village, Polanharjo District, Klaten Regency. The fertilizer subsidy policy is one of the fiscal policies aimed at increasing agricultural productivity and food security, as well as improving farmers' welfare by setting the Highest Retail Price (HET) of fertilizer. The data used in this study are primary data. Data collection was carried out by survey method through a questionnaire given to rice farmers as a sample that are using subsidized fertilizer. The method includes Benefit Incidence analysis to determine the progressivity of fertilizer subsidy by distributing government spending into different community groups based on land area and income. The second method is quantitative descriptive to determine the effectivity of subsidized fertilizer policy based on indicators of the right price, right amount, right time, and right place. The results showed that the fertilizer subsidy in Sidowayah Village, Polanharjo Subdistrict, Klaten Regency was a progressive policy based on land area groups, even though the smallest farmer groups received only 2,2% from total subsidies. However, when viewed based on income groups, the fertilizer subsidy policy is regressive. This is because the group of farmers with the highest income earns greater benefit than the other income groups. Fertilizer subsidy policy which is measured based on indicators of the right price, right amount, right time, and right place shows the results that have not been effective.